Risk transfer with CDOs and systemic risk in bankingfam - Jan Pieter Krahnen; Christian Wilde (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
Large banks often sell part of their loan portfolio in the form of collateralized debt obligations (CDO) to investors. In this paper we raise the question whether credit asset securitization affects the cyclicality (or commonality) of bank equity values. The commonality of bank equity values reflects a major component of systemic risks in the banking market, caused by correlated defaults of loans in the banks' loan books. Our simulations take into account the major stylized fact of CDO transactions, the nonproportional nature of risk sharing that goes along with tranching. We provide a theoretical framework for the risk transfer through securitization that builds on a macro risk factor and an idiosyncratic risk factor, allowing an identification of the types of risk that the individual tranche holders bear. This allows conclusions about the risk positions of issuing banks after risk transfer. Building on the strict subordination of tranches, we first evaluate the correlation properties both within and across risk classes. We then determine the effect of securitization on the systematic risk of all tranches, and derive its effect on the issuing bank's equity beta. The simulation results show that under plausible assumptions concerning bank reinvestment behaviour and capital structure choice, the issuing intermediary's systematic risk tends to rise. We discuss the implications of our findings for financial stability supervision.
urn:nbn:de:hebis:30-25959
Keywords: G28; 330; Risk Transfer; Systematic Risk; Systemic Risk; Bankgeschäft; Kreditsicherung; Risiko; Monte-Carlo-Methode